Rancang Bangun Alat Ukur Kecepatan Tendangan pada Latihan Olahraga Pencak Silat menggunakan Sensor Sharp berbasis Mikrokontroler Arduino Uno - Yanda, Randi Tri; Jaya, Putra (TSAQOFAH, 2025)
The advancement of technology offers significant opportunities for developing effective training aids, including in the field of pencak silat. One crucial aspect of pencak silat is kick speed, which directly influences the effectiveness of an athlete’s offensive and defensive actions. This study aims to design and develop an automatic kick speed measurement device utilizing two Sharp distance sensors integrated with an Arduino UNO microcontroller and a Real Time Clock (RTC) module. The sensors are positioned in parallel at a distance of 30 cm, with the system initiating time measurement when the foot passes the first sensor and stopping when it passes the second. The recorded time and distance are used to calculate kick speed, which is displayed in real-time on an LCD screen. The device design follows the waterfall method, encompassing stages of analysis, design, implementation, and testing. Test results demonstrate that all input, control, and output subsystems function optimally and are capable of delivering accurate and automated measurements. The validity of the device was assessed using Aiken’s V method and confirmed to be suitable for use in pencak silat training. The study concludes that the developed kick speed measurement tool presents an innovative solution to support the objective, efficient, and technology-based evaluation of athlete performance.